Detecting Pesticide Residue by Using Modulating Temperature Over a Single SnO2-Based Gas Sensor - Zengliang Yu (Sensors, 2003)
A new rapid detecting method (called dynamic measurements ) was reported to detect and distinguish the presence of two pesticide gases in the ambient atmosphere. The method employed only a single SnO2-based gas sensor in a rectangular temperature mode to perform the qualitative analysis of a binary gas mixture (acephate and trichlorphon) in air. Polar plots was used for quantitative analysis which the feature extraction was performed by FFT. Experimental results showed that high selectivity of the sensor achieved in the range of 250~3000C and modulating frequency 20mHz, one can easily observe the qualitative difference among the response to pure acephate and trichlorphon gases of the same concentration and to the mixture, and the concentration of pesticide gases can be obtained based on the changes of polar plots.